2015
DOI: 10.17507/jltr.0606.06
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Students’ Willingness to Communicate and Success in Learning English as a Foreign Language

Abstract: Abstract-Background:Willingness is an important factor that is instrumental in carrying out an activity successfully. Learning a foreign language is useful for having a meaningful and effective way of communication with different members of a society. This paper examines willingness among Saudi students towards learning English as a second language. It will also explore some of the difficulties that are faced by students learning English. Method: The paper used mixed methodological approach i.e. qualitative (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Al-Mohanna (2011), for example, examines aspects of classroom interaction which negatively impact the development of oral communication among university learners. Alqahtani (2015) investigates the difficulties faced by Saudi language learners that surrounds their willingness to learn English. Rafada and Madini (2017) study speaking-related anxiety in English language university classrooms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Mohanna (2011), for example, examines aspects of classroom interaction which negatively impact the development of oral communication among university learners. Alqahtani (2015) investigates the difficulties faced by Saudi language learners that surrounds their willingness to learn English. Rafada and Madini (2017) study speaking-related anxiety in English language university classrooms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In relation to research methodologies, quantitative methods which rely on questionnaires and surveys are commonly employed in language research within the Saudi context (e.g., Al-Khotaba, Alkhataba, Abdul-Hamid & Bashir, 2019;Alqahtani, 2015;Alrasheedi, 2020;Eissa, 2019;Javid, Al-Asmari, & Farooq, 2012, Soomro & Farooq, 2018. Qualitative methods, in contrast, do not seem to be similarly popular.…”
mentioning
confidence: 99%
“…Many studies have been conducted to investigate some factors that related to L2 WTC. It was found that The L2 willingness to communicate has correlation to students' motivation (Hashimoto, 2002), integrative motivation (Peng, 2007), (Alqahtani, 2015) gender (Nadafian & Mehrdad, 2015), multiple intelligence (Mohammadzadeh & Jafarigohar, 2012). motivation, social and culture are several factors that affects students' willingness to communicate in English which effect students' success in learning English (Alqahtani, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that The L2 willingness to communicate has correlation to students' motivation (Hashimoto, 2002), integrative motivation (Peng, 2007), (Alqahtani, 2015) gender (Nadafian & Mehrdad, 2015), multiple intelligence (Mohammadzadeh & Jafarigohar, 2012). motivation, social and culture are several factors that affects students' willingness to communicate in English which effect students' success in learning English (Alqahtani, 2015). language learning orientation (Zarrinabadi & Abdi, 2011) and social support (MacIntyre et al, 2001) also had correlation to the L2 WTC.…”
Section: Introductionmentioning
confidence: 99%
“…This general concern with textual analyses of written discourse is also echoed within investigations of English language learning and teaching in Saudi Arabia which often focus on identifying and addressing the challenges and difficulties that English language learners face. In relation to research methodology, these studies tend to rely heavily on quantitative methods, including surveys and textual analyses (e.g., Alqahtani, 2015;Alzubi d., 2017;Javid, Al-Asmari, & Farooq, 2012;Liton, 2012). Fewer studies adopt qualitative methodologies to provide deep understanding of situated uses of language (e.g., Barnawi, 2016;Ababneh, 2016;Mahboob & Elyas, 2014;Barnawi & Phan, 2015;Nazim & Hazarika, 2017).…”
Section: Introductionmentioning
confidence: 99%